Applications of Congruence to Divisibility Theory - Lemma, Mulatu; Allard, Dustin (IJRDO -JOURNAL OF MATHEMATICS, 2017)
The concept of congruence plays a big role in the theory of divisibility.In our study we master different properties of congruence and deeply investigate itsapplications to the divisibility theory. We will observe that the concept of congruence issuch a power technique in dealing with the concept of divisibility. Fermat’s andWilson’s Theorems will be studied and applied in the theory of divisibility. Severalimpressive results and applications will be discussed with different mathematicaltechniques applied.